DFT study of five-membered ring PAHs. (April 2020) - Devi, Gauri; Buragohain, Mridusmita; Pathak, Amit
Abstract: This work reports a 'Density Functional Theory' (DFT) calculation of PAH molecules with a five-member ring to determine the expected region of infrared features. It is highly possible that fullerene molecule might be originated from five-membered ring PAH molecules in the ISM. Effect of ionization and protonation on five-membered ring PAH molecule is also discussed. A detail vibrational analysis of five-membered ring PAH molecule has been reported to further compare with observations and to identify any observational counterpart. Highlights: Density Functional Theory (DFT) study of the infrared properties of five-membered ring PAHs relating Unidentified Infrared (UIR) emission bands observed in the Interstellar Medium (ISM). Spectral properties of five-membered ring PAHs are compared with its six-membered ring counterparts. Five-membered ring at the centre as well as at the edge in the structure are considered. Relative intensities and scaled frequencies are used to plot a Gaussian. Normalization has been made same across all the species in order to convert absolute intensities into relative intensities.